Analisa Pertanggungjawaban Pidana Atas Penggunaan Aset Kripto Sebagai Sarana Tindak Pidana Pencucian Uang - Adinda Melinia Sari; Sari Mandiana; Paula Paula (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research discusses the criminal act of money laundering through crypto assets and the form of criminal liability for crypto assets as an object of money laundering in Indonesia. Crypto assets function as an investment not for currency as a means of payment, but crypto assets are legally designated as digital commodity objects in the form of assets. Crypto assets have the threat of being misused as a new mode of money laundering to hide and disguise the proceeds of criminal acts. This research is structured with a statutory approach, concept approach and case approach with data collection based on literature and secondary materials.The results of the discussion of this research show that legitimate crypto assets as digital commodities can turn into illegitimate or illegal crypto assets as a result of the object of the means of criminal acts of money laundering. Money laundering through crypto assets that fulfill the elements of the criminal act of money laundering has criminal liability. The perpetrators of money laundering through crypto assets can be reached and held accountable according to the money laundering article violated in Law Number 8 Year 2010.